2011
DOI: 10.1177/0148607110395512
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adding Pyrroloquinoline Quinone to Parenteral Nutrition on Gut‐Associated Lymphoid Tissue

Abstract: Background: Experimental intravenous (IV) parenteral nutrition (PN) diminishes gut‐associated lymphoid tissue (GALT) cell number and function. PN solution cannot maintain GALT at the same level as a normal diet, even when delivered intragastrically (IG). Previous studies demonstrated pyrroloquinoline quinone (PQQ)–deficient mice to be less immunologically responsive. Because standard (STD) PN solution lacks PQQ, PQQ supplementation may prevent PN‐induced GALT changes. This study was designed to determine the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Jiro Omata et al reported that PQQ is not included in parenteral nutrient solutions for clinically treated because it has not been proven to be an essential nutrient for the body. However, in patients receiving parenteral nutrition, it is possible to prevent gastrointestinal mucosal immune disorders exists by supplementation of PQQ [35]. Cytokines play a critical role in the immune response and inflammation and can be important mediators to prevent susceptibility to infection and some gastrointestinal dysfunctions happening [36].…”
Section: Discussionmentioning
confidence: 99%
“…Jiro Omata et al reported that PQQ is not included in parenteral nutrient solutions for clinically treated because it has not been proven to be an essential nutrient for the body. However, in patients receiving parenteral nutrition, it is possible to prevent gastrointestinal mucosal immune disorders exists by supplementation of PQQ [35]. Cytokines play a critical role in the immune response and inflammation and can be important mediators to prevent susceptibility to infection and some gastrointestinal dysfunctions happening [36].…”
Section: Discussionmentioning
confidence: 99%
“…Jiro Omata et al reported that PQQ is not included in parenteral nutrient solutions for clinically treated because it has not been proven to be an essential nutrient for the body. However, in patients receiving parenteral nutrition, it is possible to prevent gastrointestinal mucosal immune disorders exists by supplementation of PQQ [35]. Cytokines play a critical role in the immune response and in ammation and can be important mediators to prevent susceptibility to infection and some gastrointestinal dysfunctions happening [36].…”
Section: Discussionmentioning
confidence: 99%
“…Across all samples, 472,760 quality sequences were of su cient quality for analysis. On average, 35,413 sequences per sample with a read length greater than 400 bp were obtained (Supplementary table 1). The top 15 phyla and genera in terms of relative abundance of the fecal bacteria are shown in Fig.…”
Section: Summary Of Microbiota Analysismentioning
confidence: 99%
“…When PQQ supplemented orally in nano-amounts alleviates the mitogens of B and T cells [118]. PQQ treatment enhances IgA level, restores mass of GALT [119] and induce immunity against bacterial or viral invasion [120], subsequent suppression by increased levels of proteins induced by IFN-β via iNOS, JAK1 and STAT1 signaling pathways (Table 7). PQQ was involved in phosphorylation of 1KKβ, p38 and nF-kB as a pre-inflammatory retort of macrophages [121] increase the number of lymphocytes and CD8+ cells (Table 3) [19].…”
Section: Pqq Role In Immunitymentioning
confidence: 99%
“…m-GDH in Escherichia coli have molecular structure and catalytic reaction site, N-terminal domain to anchor the domain in periplasmic t and activity shown by X-ray modeled structure of the α-subunit in PQQ active site [161][162][163][164][165]. The m-GDH of E.coli is a securely fixed with ubiquinone localized coenzyeme (PQQ) [120]. The structural designation of PQQ-GDH protein could be elucidated by Pfam, I-TASSER and Inter Pro Scan (Figure 22), [110].…”
Section: Bioinformatics Based Structural Analysismentioning
confidence: 99%